The role of Health and wellness tourism in sustainable territorial development - Quintela, Joana (2019)
This study intends to analyse the role of health and wellness tourism in sustainable territorial development. Under a perspective of sustainability, tourism industry contains the potential to facilitate and to contribute to quality of life of communities since the moment it combines their different interests with the visitors’ and respects the natural, cultural and economic resources of the territories. This balanced combination of factors reveals crucial for local and regional development that reveals even more important to the inner regions. Under this postulation and considering that the central region of Portugal is health and wellness tourism centre of attraction – where 50% of the total of thermal units of the country are concentrated – the main goal of this research is to evidence the potential of health and wellness tourism in local and regional development. Methodologically, this research will combine qualitative and quantitative research methods, using the delphi and survey technique among the administrators, managers and users of health and wellness units. In this paper, only an exploratory and conceptual approach is made based on the literature review. Although, the intention is to contribute to advancing knowledge in the field of health and wellness tourism, demonstrating and providing evidence in the future through the empirical research, about its potential as an element to settlement of the population on the inland regions of Portugal.